CLINICAL AND IMMUNOLOGICAL EFFICASY OF MODERN MUCOSAL VACCINE IN CHILDREN WITH RECURRENT RESPIRATORY INFECTIONS - V. V. Klimov (Вопросы современной педиатрии)
A 5-year clinical observation of 40 children with frequent respiratory infections and otorhinolaryngologic disorders at the age of from 6 months to 5 years was performed in order to assess clinical and immunological efficacy of modern mucosal vaccine. The tested medicine was shown to significantly decrease the frequency of respiratory infections and necessity of antibacterial treatment and to raise the level of serum IgA. The after-effect of the drug lasted for 1–2 years.